IMPACT OF MAHATMA GANDHI NREGA ON THE EMPOWERMENT OF RURAL WOMEN IN RAJASTHAN - Bairwa, Shyoji Lal; Meena, Sulochana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the development of any nation, the participation of every individual, class, caste and community of the society is considered important. In this concept of development, we cannot ignore the participation of women. If the women of a country are cultured, civilized and progressive in various fields, then there is no need to know what is the level of development in that country? History is a witness to the fact that the participation of women in the development of the nation has presented a standard example to the whole world. Women empowerment means the freedom of women to take decisions in social, economic, political, legal and mental fields equal to men in the cultural background of their family, community, society and nation. In a developing country like India, where the role and status of women was pathetic from the beginning, it has not improved even today, but from time to time, meaningful efforts have been made for their welfare and respect by scholars and government efforts. MNREGA is a successful step of those meaningful efforts. Women empowerment is one of the important objectives of MNREGA. This program acts as a tool to change the scenario and lifestyle of rural women. Under MNREGA, it is said that more than one-third of the distribution of work should be done by women. The sole purpose of having such a system is to promote women empowerment, to raise the morale of women and make them self-reliant. Schemes like MNREGA are promoting the feeling of empowerment in women by making them self-reliant.